Inspiratory Muscle Trainer Effectiveness in Chronic Obstructive Pulmonary Disease Rehabilitation Program - Nusdwinuringtyas, Nury; Islamadina, Balqis; Rumende, Cleopas Martin; Kamelia, Telly (Majalah Kedokteran Bandung, 2019)
Chronic obstructive pulmonary disease (COPD) is marked by persistent respiratory disturbance which results in altered health status as well as functional capacity. Pulmonary rehabilitation (PR) is a part of comprehensive therapy in patients suffering from respiratory disturbance. This study focused on inspiratory muscles exercise using the inspiratory muscle trainer(IMT), which is a form of a weight training exercise. This experiment was conducted at the COPD outpatient clinic of Dr. Cipto Mangunkusumo Hospital during the period of September 2017 until April 2018. Patients were recruited consecutively. The criteria for inclusion were stable COPD patient with GOLD criteria A-D and never received prior exercise for pulmonary rehabilitation. Patients underwent interview about their medical history followed by spirometry testing using Carefusion® and inspiratory muscle strength assessment using Micro RPM Carefusion®. The St George Respiratory Questionnaire (SGRQ) was used to assess the health status and the 6-minute walking test (6MWT) was conducted to assess the functional capacity. Subject exercised using IMT (Philips Respironic®) for eight weeks. Data were analyzed using paired t-test in statistical package for social sciences (SPSS) version 21. A total of 15 subjects with and average age of 65.6±8.40 years old were recruited. Pre-Post difference in inspiratory muscle strength was 11.31 cmH2O, showing a statistically significant impact. The significant impact was also shown clinically through the results of the Minimal Clinical Important Difference (MCID) on health status and functional capacity. The health status was evaluated using SGRQ with p exceeding 4%. A combined Pulmonary Rehabilitation (PR) and inspiratory muscles exercise program is proven to improve the health status and functional capacity. Key words: COPD, inspiratory muscle trainer, pulmonary rehabilitation, SGRQ, 6MWT Keefektifan Inspiratory Muscle Trainer Pada Program Rehabilitasi Penyakit Paru Obstruktif Kronik Penyakit paru obstruktif kronik (PPOK) ditandai dengan gangguan pernapasan yang persisten yang mengganggu status kesehatan dan kapasitas fungsional. Pulmonary rehabilitation (PR) merupakan bagian dari terapi komprehensif pasien dengan ganguan respirasi. Penelitian ini memfokuskan pada latihan otot inspirasi menggunakan inspiratory muscle trainer (IMT), suatu bentuk latihan otot pernapasan dengan pemberian beban. Eksperimen ini dilakukan di Rumah Sakit Cipto Mangunkusumo selama periode September 2017 hingga April 2018. Pasien direkrut secara consecutive sampling. Kriteria inklusi adalah pasien PPOK yang stabil dengan kriteria GOLD A-D yang belum pernah menerima latihan sebelumnya untuk rehabilitasi paru. Pasien menjalani wawancara, diuji dengan spirometri Carefusion®, dan kekuatan otot inspirasi dinilai menggunakan Micro RPM Carefusion®. St George Respiratory Questionnaire (SGRQ) digunakan untuk menilai status kesehatan dan 6-minute Walking Test (6MWT) dilakukan untuk menilai kapasitas fungsional. Subyek menggunakan alat IMT (Philips Respironic®) selama 8 minggu. Data dianalisis menggunakan SPSS versi 21 dengan uji T berpasangan. Subjek penelitian berjumlah 15 orang dengan rerata usia 65,6 ± 8,40 tahun. Kekuatan otot inspirasi awal didapatkan perubahan sebesar 11,31 cmH2O, yang memberikan dampak bermakna dilihat dengan pencapaian minimal clinical important difference (MCID) pada status kesehatan dan kapasitas fungsional. PR bersama dengan program latihanotot inspirasiterbukti memberikan hasil perbaikan status kesehatan dan kapasitas fungsional. Kata kunci: COPD, inspiratory muscle trainer, pulmonary rehabilitation, SGRQ, 6MWT